Student services : a handbook for the profession/ [edited by] John H. Schuh, Susan R. Jones, Shaun R. Harper, and associates. - Schuh, John H.; Jones, Susan R., 1955-; Harper, Shaun R., 1975-; Komives, Susan R., 1946- (San Francisco : Jossey-Bass, 2011)
'Since it was first published, Student Services has become a classic reference in the field. In this edition, a new panel of student affairs scholars examines the student experience in higher education, the evolution of the role of student affairs professionals, and the philosophies, ethics, and theories that guide the practice of student affairs work. This new edition covers a broad range of relevant topics including legal issues, managing student affairs programs, leadership, conflict resolution, community development professionalism, and developing institutional partnerships. It also addresses the future of the practice'--
Rev. ed. of: Student services / Susan R. Komives, Dudley B. Woodard, Jr., and associates. 4th ed. 2003.
Includes bibliographical references and indexes.
Keywords: Student affairs services -- United States -- Handbooks, manuals, etc; College student development programs -- United States -- Handbooks, manuals, etc; Counseling in higher education -- United States -- Handbooks, manuals, etc